2001
DOI: 10.1128/aem.67.4.1575-1580.2001
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Trichothecene-Producing Fusarium Species in Harvested Grain by Competitive PCR To Determine Efficacies of Fungicides against Fusarium Head Blight of Winter Wheat

Abstract: We developed a PCR-based assay to quantify trichothecene-producing Fusarium based on primers derived from the trichodiene synthase gene (Tri5). The primers were tested against a range of fusarium head blight (FHB) (also known as scab) pathogens and found to amplify specifically a 260-bp product from 25 isolates belonging to six trichothecene-producing Fusarium species. Amounts of the trichothecene-producing Fusarium and the trichothecene mycotoxin deoxynivalenol (DON) in harvested grain from a field trial desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
127
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(139 citation statements)
references
References 40 publications
11
127
0
1
Order By: Relevance
“…This observation was corroborated by several scientific reports (Edwards et al 2001;Paul et al 2008;Pirgozliev et al 2002). Finally for prothioconazole Paul et al (2008) mentioned decreased DON levels.…”
Section: Fungicides To Control Mycotoxin Productionsupporting
confidence: 78%
See 1 more Smart Citation
“…This observation was corroborated by several scientific reports (Edwards et al 2001;Paul et al 2008;Pirgozliev et al 2002). Finally for prothioconazole Paul et al (2008) mentioned decreased DON levels.…”
Section: Fungicides To Control Mycotoxin Productionsupporting
confidence: 78%
“…For tebuconazole it is generally accepted that it causes a reduction in the biosynthesis or DON level (Edwards et al 2001;Haidukowski et al 2005;Ioos et al 2005;Paul et al 2008;Simpson et al 2001;Zhang et al 2009a) and the trichothecene nivalenol (NIV) (Ioos et al 2005). Information on another triazole fungicide propiconazole is contradictionary.…”
Section: Fungicides To Control Mycotoxin Productionmentioning
confidence: 99%
“…Theoretically, Fusarium mycotoxins can be produced on every plant and all plant parts infested by toxigenic Fusarium species. Over the last ten years, detection of mycotoxins and toxigenic Fusarium species has advanced signifi cantly with the development of PCR-based techniques (13)(14)(15)(16). However these techniques are still not widely used because they are expensive.…”
Section: Discussionmentioning
confidence: 99%
“…High disease pressure of Fusarium is not automatically related to a higher DON content (Everlange in 2008, severity: 36% and DON: 301 mg/kg). Edwards et al (2001) suggested that some pathogens do not produce mycotoxins, which means that mycotoxin contamination is not related to visual symptoms of disease severity. Opinions also vary strongly on the existence of a relationship between DON and the amount of FHB pathogen (Isebaert et al, 2009).…”
Section: Discussionmentioning
confidence: 99%